(untitled) - Wunsch, A. David (Reading, Mass, 2005)
Contents: Complex numbers; the comples fuction and its dervative; integration in the complex plane; conformal mapping and some of its application.
Giải tích phức
Keywords: Functions of complex variables,Hàm số biến số phức